STRATEGI PENJUAL JAGUNG REBUS(PJR) DALAM MENARIK PELANGGAN DI DESA AMESIU KECAMATAN PONDIDAHA KABUPATEN KONAWE - Barlin Barlin; Ashmarita Ashmarita (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2018)
This research aims to find out the reasons of people selling boilded corn and to find out the strategies of people that selling boiled corn to preserve selling boiled corn in Pondidaha District, Konawe Regency. This research use theory of adaptation strategy by John William Bennet. The method of this study is to use the observation method and observation in a holistic-integrative manner, in-depth descriptive and qualitative analysis. The results of this study are known to the Boiled Corn Sellers (PJR) using several strategies in selling boiled corn in Amesiu Village, Pondidaha District, Konawe Regency. Conclusion 1). The reason people sell corn here is interpreted as an element or thing that can affect a situation or someone to do something. Availability of Human Resources as well as Natural Resources is sufficient, which is the reason for boiled corn sellers to continue to exist today. 2). The strategy of boiled corn sellers is an attempt to find out how everything related to a particular goal could be achieve, so that boiled corn sellers still exist in running their businesses and can attract the purchasing power of road users, while the strategies are as follows: (a) lifting pan cover, (b) merchant stall smile, how to dress, employ beautiful women, additional menus, (c) give discounts, (d) SKSA (pretentious to get closer), (e) give cellphone number. From several strategies carried out by boiled corn sellers with the intention of attracting buyers of road users to take a break from the weary journey to taste snacks offered by boiled corn sellers Keywords: strategy, boilded corn, seller, Desa Amesiu